PENGARUH PROFESIONALISME TERHADAP PRODUKTIVITAS PEGAWAI PADA BADAN PUSAT STATISTIK PROVINSI SULAWESI SELATAN - Usman Usman (P3M STIEM BONGAYA, 2020)
This research aims to find out if the effect of professionalism variables on employee productivity variables in the Central Bureau of Statistics of South Sulawesi Province. Data collection using primary data obtained from questionnaires using simple random sampling techniques. The population is all employees of the Central Bureau of Statistics of South Sulawesi Province, a total of 90 employees, while the sample taken amounted to 40 respondents. The results of the questionnaire have tested its validity and reliability, and have also tested classic assumptions in the form of tests of normality, multicollinearity and heteroskedastisitas. The data analysis method uses multiple regression techniques. The results showed that the proposed hypothesis was accepted because it showed positive and significant hypothetical test results, against professionalism variables to employee work productivity variables The results showed that the proposed hypothesis was accepted because it showed positive and significant hypothetical test results, against professionalism variables to employee work productivity variables. Keywords : Professionalism, Employee Work Productivity